Mechanical Performance Analysis of Interlocking Compressed Earth Bricks with Various Kenaf Fiber Length for Sustainable Construction Material - Noor Hannah binti Moideen; Ruzaimah binti Razman (Journal of Structural Monitoring and Built Environment, 2026)
This study examines the influence of kenaf fiber length on the mechanical properties of Interlocking Compressed Earth Bricks (ICEB). A 1:3:2 mix ratio of cement, soil, and sand with 0.75% kenaf fiber and stabilizer was used, and total KF-ICEB for this study is 54 brick were tested with 5 different kenaf fiber lengths (20mm, 30mm, 40mm, 50mm, 60 mm) to analyze their impact on strength and durability. Compressive strength results showed that all bricks did not pass the minimum requirement of 2.8 N/mm² for non-load-bearing applications. Flexural strength peaked at 1.91 MPa after 28 days of curing for 50 mm KF-ICEB, but the curing process revealed suboptimal hydration and bonding. Water absorption tests indicated 24.21%, exceeding the 15% baseline, indicating poor fiber distribution at 20 mm and optimal water retention at 50 mm 18.9%, closer to the control. However, uneven mixing caused clumping of fibers, which likely affected the bricks’ overall quality and performance. The findings suggest the need for improved mixing methods and optimized ratios to maximize ICEB strength and durability.